Effect of Strenuous Exercise on Various Blood Parameters in Polo Horses at High Altitude (3,734 M) - Nabi, Habibun; Khan, Sohail; Shah, S. Rahimullah; Siddique, Hazrat Salman; Khan, Shakirullah; Hussain, Ibrar; Ali, Syed Imtiaz (American Scientific Research Journal for Engineering, Technology, and Sciences, 2021)
Horses require heaps of energy in order to perform well. Proper care and management should therefore be provided to the racehorses so as to keep they perform at their optimum. The experiment used for normal horses. The blood samples were collected in the morning before subjecting the horses to polo match/ strenuous exercise and immediately after the physical activity. Various blood tests such as the complete blood count, lipid, protein tests were done. Significant elevations in the white blood cells (WBC), hemoglobin (Hb) and some serological parameters in the blood polo horses were recorded after exercise. This study confirmed the findings of exercise on different blood parameters which can be possibly used as an index of fitness in horses.